Gadolinium-loaded LTL nanosized zeolite for efficient oxygen delivery and magnetic resonance imaging. Issue 9 (5th April 2023) - Amedlous, Abdallah; Hélaine, Charly; Guillet-Nicolas, Rémy; Lebedev, Oleg; Valable, Samuel; Mintova, Svetlana
Abstract : The search for efficient gas carriers for biomedical applications presents a challenging task due to the kinetics of gas adsorption/desorption. This article presents a novel approach utilizing Gd-LTL zeolite crystals for oxygen delivery combined with an MRI study. Abstract : The key challenges in finding efficient gas carriers for biomedical applications are related to the kinetics of gas adsorption/desorption of non-toxic materials over appropriate time intervals, specifically targeting the affected area. Herein, we report the preparation of nanosized gadolinium (Gd-LTL) zeolite crystals with a diameter of 10–15 nm for oxygen delivery combined with a magnetic resonance imaging (MRI) study. The partial ion-exchange of potassium (K) extra framework cations used for the synthesis of nanosized K-LTL zeolite with paramagnetic gadolinium (Gd, 1.53 wt%) changed its adsorption capacity for O2 considerably. The nanosized Gd-LTL zeolite retained high colloidal stability and remarkable crystallinity, and no leaching of Gd ions was observed. In addition, the in vitro toxicity study performed in human glioblastoma-derived cell lines revealed that nanosized K-LTL and Gd-LTL nanosized zeolites showed no toxicity, even at high concentrations. This study provides promising guidelines regarding the design of smart biocompatible nanosized zeolites coupling gas-delivery and MRI properties.